2014
DOI: 10.1142/s0219199714500473
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Gear–Grimshaw system on a periodic domain

Abstract: Abstract. This paper is devoted to the study of a nonlinear coupled system of two Korteweg-de Vries equations in a periodic domain under the effect of an internal damping term. The system was introduced Gear and Grimshaw to model the interactions of two-dimensional, long, internal gravity waves propagation in a stratified fluid. Designing a time-varying feedback law and using a Lyapunov approach we establish the exponential stability of the solutions in Sobolev spaces of any positive integral order.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…However, the stabilization results for system (1.1)-(1.2) was first obtained in [4], when the authors considered the system in a periodic domain. Recently, Capistrano-Filho et al [3] proved a result which extends the result proved by Dávila [4], which one was proved only for s ≤ 2. More precisely, in [3], they showed that for any fixed integer s ≥ 3, the solutions are exponentially stable in the Sobolev spaces H s p (0, 1) := {u ∈ H s (0, 1) : ∂ n x u(0) = ∂ n x u(1), n = 0, .…”
Section: State Of Artsupporting
confidence: 52%
“…However, the stabilization results for system (1.1)-(1.2) was first obtained in [4], when the authors considered the system in a periodic domain. Recently, Capistrano-Filho et al [3] proved a result which extends the result proved by Dávila [4], which one was proved only for s ≤ 2. More precisely, in [3], they showed that for any fixed integer s ≥ 3, the solutions are exponentially stable in the Sobolev spaces H s p (0, 1) := {u ∈ H s (0, 1) : ∂ n x u(0) = ∂ n x u(1), n = 0, .…”
Section: State Of Artsupporting
confidence: 52%
“…Theorem 1.1. For almost all quadruples (a, c, d, r) ∈ (0, ∞) 4 the following property holds. For any fixed…”
Section: State Of the Artmentioning
confidence: 99%
“…The internal stabilization problem has also been addressed (see, for instance, [4,9,29] and the references therein). Although controllability and stabilization problems are closely related, one may expect that some of the available results will have some counterparts in the context of the control problem, but this issue is open.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations